Coupled in-nozzle flow and spray simulation of Engine Combustion Network Spray-G injector. (September 2021) - Mohan, Balaji; Badra, Jihad; Sim, Jaeheon; Im, Hong G
A coupled Eulerian-Lagrangian approach was employed to Engine Combustion Network (ECN) Spray-G simulations. The Eulerian in-nozzle flow simulation was conducted with a small plenum attached to the nozzles, and the results were fed to the Lagrangian spray simulation. For Eulerian simulation, the homogeneous relaxation model (HRM) coupled with the volume of fluid (VOF) method was used. HRM proved to be good at predicting the phase change phenomena due to vaporization mechanisms, that is, both cavitation and flash boiling. As a one-way coupling, quantities such as rate of injection (ROI), mass injected through each hole, discharge coefficient, spray plume angle and half cone angle predicted from the Eulerian simulations were used as the initial and boundary conditions for the subsequent Lagrangian spray simulations using the blob injection model. Non-flashing (Spray-G1) and flashing (Spray-G2) spray was simulated, and the results were validated quantitatively against the published data in terms of the liquid and vapor penetration lengths, and good agreements were obtained. Furthermore, the simulation predicted the liquid and gas axial velocity and sauter mean diameter for Spray-G1 condition in agreement with the droplet size and particle image velocimetry (PIV) measurements from literature.